Hate follow : a novel - Quinn-Kong, Erin (William Morrow, an imprint of HarperCollins Publishers, 2024)
Influencer Whitney Golden has it all: beautiful, photogenic children; a handsome new boyfriend; a gorgeous house; and designer clothes and beauty products that arrive on her doorstep every day. After spending years building her brand as a widowed mother of four (including twins!) to over a million followers, the thirty-seven-year-old is at the peak of her career. But it all comes to a screeching halt when Mia, her teenaged daughter, announces she's tired of the social media life. She wants nothing more to do with her mother's online brand, and demands that not just she, but her siblings and their deceased father be removed from Whitney's Instagram, blog, and just about everywhere else on the internet. When Whitney doesn't agree, Mia does the unthinkable: She sues her mother. What started as a family spat turns into a monumental case about child privacy, individual agency, and modern parenting that shatters Mia and Whitney's relationship and wreaks havoc on both their lives. As the case ignites a media firestorm and unrelenting online bashing from a Greek chorus of internet snarkers, Whitney has to decide whether she's willing to risk everything she's built to win back her daughter.